Caring Model Development in Improving Quality of Nursing Services in Tasikmalaya - Suprapti, Betty; Herliana, Lia; Yuningsih, Aneng (INDOGENIUS, 2025)
Background: Caring is needed to improve services for consumers, in this case, patients. The development of caring behavior models in hospitals is essential in improving the quality of nursing services so that it impacts the number of patients treated. Purpose:  to identify the need for a caring model in improving the quality of nursing care at the Tasikmalaya Islamic Hospital, Indonesia Method: The research method uses a qualitative design with a phenomenological approach involving elements of management, nurses, and patients being treated. There were 13 participants consisting of 8 nurses as critical participants and five patients currently treated as validators. Data retrieval through in-depth interviews and focus discussions is then analyzed through content analysis. Results: The results obtained were four major themes and two sub-themes related to hospital development and the required caring model. A model of serving with "HEART" is obtained from the hospital's vision, nurse's, and patient's expectations of caring behavior. Conclusion: Nurses perceive caring behavior as serving wholeheartedly, prioritizing patient comfort, and communicating effectively and ethically. The caring model of serving with "heart" can be presented and implemented to improve nursing care services..